Zoological names on -ok in the confixes subsystem of the Ukrainian nouns (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The features derivational structure and semantics of zoological names on -ok were reviewed in the article and their place in the confixes subsystem of the Ukrainian nouns was determined. The activity of confixes was leant, specifically formants with the postpositive component -ok in the formation process of the zoological names.
Keywords: confixes; derivation structure; zoon